Influence of heavy metals on thermal conductivity of clay as a building material. Issue 1 (2nd January 2019) - Babatunde, Egbeyale Godwin; Adeyemo, Adegoke James
ABSTRACT: Thermal conductivity of contaminated clay is an emerging field of interest in building construction. This study investigated the influence of some heavy metals on thermal conductivity of clay. The objective of this study is to investigate the influence of heavy metal in clay for energy-efficient in building constructions. The clay sample was collected from clay deposit and prepared. The samples were mixed (contaminated) with nitrates of Pb, Fe, Zn, Ni and Cu at different concentrations and slabs then were formed. The thermal conductivity of clay slabs were measured to determine the suitability of contaminated clay as building material for heat emitting modern equipment room. The thermal conductivity of clay slabs contaminated with nitrate of Pb, Fe, Zn, Ni and Cu ranged 0.06–0.15 Wm −1 K −1 ; 0.06–0.18 Wm −1 K −1 ; 0.06–0.22 Wm −1 K −1 ; 0.06–0.19 Wm −1 K −1 and 0.06–0.38 Wm −1 K −1, respectively. Results showed that thermal conductivity of clay increases with increase in the concentration of heavy metal absorbed by the clay to an optimum level. Hence, heavy metals influenced the thermal properties of clay building material.